INTERPRETATION OF “HAMD” AND “NA’T” IN ARTISTIC LITERATURE (BASED ON THE WORKS OF MAJZUB NAMANGANI) (World Bulletin of Social Sciences, 2025)
This article examines the interpretation of the genres of Hamd (praise of God) and Na‘t (praise of the Prophet Muhammad, peace be upon him) in the works of Majzub Namangani, a prominent 18th–19th century Sufi poet, scholar, and Naqshbandi sheikh. Drawing upon Qur’anic verses, Hadith, and Sufi teachings, Majzub’s poetry reflects his deep spiritual devotion, philosophical worldview, and aesthetic mastery. His Hamd poems emphasize the greatness of the Creator as the origin of existence, while his Na‘t verses express sincere love and reverence for the Prophet Muhammad as “rahmatun lil-‘alamin” (mercy to all worlds). The poet’s artistic skill is evident in his use of classical prosody (aruz), rhyme, and rhetorical devices such as metaphor, simile, and antithesis. The study highlights Majzub Namangani’s significant contribution to the enrichment of classical Uzbek literature and to the development of religious-mystical poetic traditions